Study of serum creatinine phosphokinase and serum lactate dehydrgenase as prognostic markers in organophosphorus poisoning - G., Raghu; Gangannavar, Ayyanagouda A.; K., Manoj Kumar B.; Rajoor, Umesh (International Journal of Advances in Medicine, 2020)
Background: Organophosphorus (OP) compounds are insecticides which are widely used in agriculture. Acute organophosphorus poisoning is an important cause of morbidity and mortality in developing countries like India. In a limited resourced country like India, we need cheap and easily measurable biomarkers for predicting prognosis. Objective was to estimate creatinine phosphokinase and serum lactate dehydrgenase as prognostic markers in acute organophosphorus poisoning. Methods: Total 94 cases of OP poisoning admitted to KIMS Hospital, Hubbali between January 1st 2017 to December 31th 2017 were studied. Detailed history, clinical examination and lab investigations like pseudo cholinesterase, serum LDH and serum CPK were carried out. Peradeniya OP poisoning scale was applied to all study subjects and the severity of OP poisoning was graded as mild, moderate, severe. Data obtained was analysed by different statistical methods. Results: OP poisoning is more common in adults of age group between 20 - 30 years, Incidence is was more in male patients, Mortality rate is 12.8%. Mean values of serum LDH, serum CPK were negatively correlated with pseudcholinesterase levels and it was statistically significant. Correlation between the severity of OP poisoning (based on Peradenyia score) and biochemical parameters like serum CPK, serum LDH, was statistically significant. Conclusions: The correlation between the severity of OP poisoning and biochemical parameters was statistically significant and they are usefull in predicting development of respiratory failure.